Unilateral severe gynecomastia in a 14 year-old adolescent with neurofibromatosis type 1 undergoing endoscopic mastectomy: a case report - Shang, Fangjian; Xi, Bo; Qiu, Duojun; Chen, Xin; Wang, Yifang; He, Meng; Liu, Bo; Zhao, Zengren (Frontiers in Medicine, 2024)
Gynecomastia can be caused by neurofibromas but has rarely been reported. The present case report describes the clinical appearance, diagnosis, and therapy of a rare combination of a 14 year-old adolescent male unilateral severe gynecomastia with NF-1 neurofibromatosis. In this particular case, we successfully performed minimally invasive surgery using endoscopic mastectomy, which not only resulted in a satisfactory appearance but also confirmed the presence of neurofibroma type 1 by detecting typical immunohistochemical indicators associated with the disease. Additionally, we analyzed the gene responsible for the disease, c.1431del: p. F477Lfs*21, based on the patient’s family history.